2009
DOI: 10.17305/bjbms.2009.2777
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion-Transmitted Infections in Haemophilia Patients

Abstract: One of the largest therapeutic problem during the continuous treatment of the patients with Hemophilia A and B, are viral infections as Hepatitis B and C, and HIV, and the other infective diseases, which can be transmitted by the transfusion of blood products. Th e aim of this study is to analyze the complications of the hemophiliacs in Kosovo which have been treated with fresh frozen plasma, cryoprecipitate and concentrated products of FVIII and FIX. We have tested  patients with hemophilia A or B and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Zhubi et al. showed that in patients with haemophilia in Kosovo, HCV infection was present in 38.7%, whereas HBV was present in 2.7%, and HIV infection was found in 1.4% [15]; their figure for HCV prevalence was very similar to ours. According to Alavian et al.…”
Section: Discussionsupporting
confidence: 85%
“…Zhubi et al. showed that in patients with haemophilia in Kosovo, HCV infection was present in 38.7%, whereas HBV was present in 2.7%, and HIV infection was found in 1.4% [15]; their figure for HCV prevalence was very similar to ours. According to Alavian et al.…”
Section: Discussionsupporting
confidence: 85%
“…HCV infection is considered one of the most relevant causes of morbidity and mortality in patients with hereditary bleeding disorders, especially hemophilia A. Most hemophilia A patients have been infected by HCV during receiving plasma derivatives before the implementation of compulsory blood donors screening [Zhubi et al, 2009; Zoulim and Bailly, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…HCV infections in cases of age under 18 years was only 9.5%. [17] Morfini, et al . from Italy studied on 708 hemophiliacs patients, infused for the first time before 1985 (group A) and 80 patients, infused for the first time between 1985 and 1991 (group B).…”
Section: Discussionmentioning
confidence: 99%